Supercritical metalens at h-line for high-resolution direct laser writing - Jichao Fu; Mengting Jiang; Zeng Wang; Yi Fan Chen; Yuanda Liu; Qing Yang Steve Wu; Ai Jia Sim; Jiang Wang; Mingxi Chen; Ziyu Wang; Jie Deng; Xiao Song Eric Tang; et al. (Opto-Electronic Science)
Supercritical lens (SCL) can break the diffraction limit in the far field and has been demonstrated for high-resolution scanning confocal imaging. Its capability in sharper focusing and needle-like long focal depth should allow high-resolution lithography at violet or ultraviolet (UV) wavelength, however, this has never been experimentally demonstrated. As a proof of concept, in this paper SCLs operating at 405 nm (h-line) wavelength with smaller full-width-at-half-maximum focal spot and longer depth of focus than conventional Fresnel zone lens while maintaining controlled side lobes are designed for direct laser writing (DLW) lithography. Aluminum nitride (AlN) with a high refractive index and low loss in UV-visible range is used to fabricate nanopillar-based metasurfaces structure for the metalens. Grating arrays with improved pitch resolution are fabricated using the SCLs with sub-diffraction-limit focusing capability. The AlN-based metasurface for SCLs at short wavelength for DLW could extend further to UV or deep UV lithography and might be of great interest to both the research and industry applications.